2020
DOI: 10.1186/s40104-020-00500-y
|View full text |Cite
|
Sign up to set email alerts
|

MiR-214-3p promotes proliferation and inhibits estradiol synthesis in porcine granulosa cells

Abstract: Background Granulosa cells (GCs) proliferation and estradiol synthesis significantly affect follicular development. The miR-214-3p expression in the ovarian tissues of high-yielding sows is higher than that in low-yielding sows, indicating that miR-214-3p may be involved in sow fertility. However, the functions and mechanisms of miR-214-3p on GCs are unclear. This study focuses on miR-214-3p in terms of the effects on GCs proliferation and estradiol synthesis. Results Our findings revealed that miR-214-3p pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Lysates from goat testes and LCs and western blot analysis procedures were performed as previously described (Gao et al, 2019; Shi et al, 2020). Goat testes and LCs were harvested at the indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…Lysates from goat testes and LCs and western blot analysis procedures were performed as previously described (Gao et al, 2019; Shi et al, 2020). Goat testes and LCs were harvested at the indicated time points.…”
Section: Methodsmentioning
confidence: 99%
“…However, only two miRNAs (miR‐214 and miR‐101) have been shown to influence the expression of CYP11A1 in large livestock without deeply mechanism investigation (X. An et al, 2020; Shi et al, 2020). In this study, we found that miR‐365‐3p induced GC apoptosis by directly targeting and inhibiting the expression of CYP11A1, indicating that CYP11A1 is a novel direct functional target of miR‐365‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…Real-Time PCR (RT-qPCR) Experiment. Relative mRNA levels of MAM-related genes (mitofusin 1, Mfn1 and mitofusin 2, Mfn2) were assessed according to the work of Shi et al 26 Total RNA extraction was performed through an RNA extraction kit (Invitrogen Bioscience), and cDNA preparation and RT-qPCR were performed using a cDNA synthesis kit and ChamQ SYBR qPCR Master Mix (Vazyme, Nanjing, China). Supporting Table S2 enlists the sequence of primers.…”
Section: Mitochondria Isolation and Mitochondrial Membrane Potential ...mentioning
confidence: 99%